Interfaith Debate Through Youtube Media as an Effort to Educate and Fortify the Faith of the Ummah - Purwatiningsih, Sri Desti; Ekowati, Sri (Technium Social Sciences Journal, 2022)
The da'wah method through youtube media is a method used by Muslim debaters in conveying da'wah messages so that the da'wah message is conveyed according to the objectives to the listeners and viewers of the youtube channel so that Muslims are fortified with their faith so that they are not easily influenced and not easy to be converted by other religions. To facilitate and attract a broader audience in the world of da'wah and broadcast or debate between Islam and Christianity, Muslim and Christian apologists or debaters use effective communication media through online media, one of which is YouTube. The delivery of messages of truth must be systematically arranged so that the mission of this ministry can run efficiently and effectively. The research approach used is qualitative with nethographic research methods, namely the method used to understand the culture of social media users. The culture referred to here is social media (Youtube) as a safe space for social media users to share information. Netnography is a method for social media users' behavior (culture) or habits.